ANALISIS FAKTOR-FAKTOR PENYEBAB KETIDAKDISIPLINAN BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI 19 KOTA JAMBI - Istiana, Nurul; Yahuda, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the finding of indiscipline in learning behavior among class VII G students at SMP Negeri 19 Jambi City. Learning discipline is very important because it is related to compliance with rules, responsibility in doing assignments, and seriousness when attending lessons. The research used a descriptive qualitative approach with observation, interview, and documentation techniques, then analyzed through the stages of summarizing, presenting, and drawing conclusions and tested with triangulation. The results of the study showed that the forms of indiscipline that often occurred were arriving late, chatting during class, sleeping in class, leaving without permission, and not paying attention to the teacher. The causes came from internal factors of the students such as lack of motivation and laziness, as well as external factors such as lack of parental attention, peer influence, less interesting learning methods, and excessive use of gadgets. Efforts were made in the form of cooperation between teachers, schools, and parents so that students can be more disciplined in learning.